FINANCIAL PERFORMANCE AND STOCK PRICES: HOW PRICE EARNING RATIO SHAPES CROSS-SECTOR RELATIONSHIPS IN THE STOCK EXCHANGE - Basri, Basri; Irnandas, Muh.; Herianti, Herianti (Jurnal Akuntansi dan Keuangan (JAK), 2025)
This research aims to analyze the influence of the price-earning ratio as a moderating factor on share prices on the Indonesia Stock Exchange by considering cross-sector differences. The data analysis method uses panel data multiple regression with a fixed effect model approach. Financial performance data was obtained from 72 companies listed on the Indonesia Stock Exchange for the 2018–2022 research period. The research results show that the DER variable has a significant negative effect, DAR has a significant positive effect, ROA has an insignificant positive effect, and ROE has an insignificant positive effect on stock prices. Furthermore, the results of the moderation test show that PER is unable to moderate the influence of DER on share prices. However, PER is able to moderate the influence of DAR, ROA, and ROE on share prices. The results of this research provide insight for academics and implications for policymaking in the Indonesian capital market to understand how the role of PER can influence the relationship between financial performance and share prices in the context of cross-sector companies.